Pola Deformasi (Deformation Pattern) Mineralisasi Emas Sulfida Rendah di Zona Neo-Tektonik Selat Sunda - Dudi Nasrudin Usman; Nana Sulaksana; Febri Hirnawan; Iyan Haryanto (PROMINE, 2018)
The Sunda Strait is one of the zones of the Eurasian plate encounters with fairly active Indian plates. This can be seen based on volcanic activity that occurred in the region of Mount Krakatau. But there are unique things that are important to learn is tectonic movement with geological forces that work to produce cracks in rocks, the formation of volcanoes and cracks that occur produce mineralized zones, especially in the Formation of Honje and Formation Cipacar and more widely known as Bayah Dome. The presence of mineralization of the Honje Formation and Cipacar Formation is particularly located in the District of Cimanggu, Mangku Alam Village, the existence of gold mining activities proves that the mineralization of the region has the potential of economy. The presence of mineralization will not be separated from the presence of rock fractures in the two formations that have different geological age of the Late Miocene and Plistocene. Both formations are hindered by the presence of unconformity fields. This study aims to prove the extent of tectonic activity occurring in the Honje Formation with the final Miocene age forwarded to the Cipacar Formation even though obstructed by the field of nonconformity with the results of field data processing based on the value of RMR and RQD value. Both parameters are also studied to determine the extent to which the RQD value determines the magnitude of the grade value of Gold (Au). The distribution of RMR value and rock RQD value is taken from 2 different rock units, ie, andesite rock units in Honje Formation and tuff rock units in Cipacar Formation, based on the data distribution around 125 RMR observation points and 117 RQD observation points in the field are processed by using method test the average difference of the two parameters from 2 different rock units. In addition, the RQD value was correlated to the high level of gold content using correlation regression test of 78 data content and RQD value. Results of processing and discussion of data indicate that between the value of RMR in andesit unit and tuff unit there is no difference in value means H0 accepted by tcount = 0.556 <ttable = 1.995, as well as the difference test average RQD value where the results show that there is no difference between the average value of RQD andesite rock units in Honje Formation and tuff rock units in Cipacar Formation with tcount = 1.714 <ttable = 1.995, based on the results of data processing it can be explained that the tectonic activity in Honje Formation with the final Miocene age is forwarded to Cipacar Formation even if obstructed the field of dissonance means that tectonic activity of the region is inferred as neotectonic activity of West Java. In addition, one more thing that can be concluded that the relationship of RQD with Gold content (Au) based on statistical test the greater the value of RQD then the value of gold content (Au) the greater the test results regression correlation value PValue (Significance) = 0.013 with the equation y = -0.715x + 75.882 value R2 42.39%. Because Significance value> 0.05 then H0 DENIED, so H1 accepted, where the higher the value of the Big Au content then the RQD Value the greater.